2018
DOI: 10.1096/fj.201800430r
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic hypoxia‐inducible factor 2α deficiency ameliorates pathological retinal neovascularization via modulation of endothelial cell apoptosis

Abstract: A hallmark of proliferative retinopathies, such as retinopathy of prematurity (ROP), is a pathological neovascularization orchestrated by hypoxia and the resulting hypoxia-inducible factor (HIF)-dependent response. We studied the role of Hif2α in hematopoietic cells for pathological retina neovascularization in the murine model of ROP, the oxygen-induced retinopathy (OIR) model. Hematopoietic-specific deficiency of Hif2α ameliorated pathological neovascularization in the OIR model, which was accompanied by enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…Efficient removal of damaged and/or dead cells by "professional phagocytes" such as microglia and macrophages is a critical process for maintaining tissue homeostasis. Several previous studies suggest that a close interplay between myeloid and vascular components exists in different settings that may involve inflammation, cell death, and clearance of dead cells [5,6,11,35]. Here, we demonstrate a role of SOCS3 in mononuclear phagocytes for the regulation of efferocytosis of apoptotic/dead endothelial cells, which can modulate ex vivo angiogenesis.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Efficient removal of damaged and/or dead cells by "professional phagocytes" such as microglia and macrophages is a critical process for maintaining tissue homeostasis. Several previous studies suggest that a close interplay between myeloid and vascular components exists in different settings that may involve inflammation, cell death, and clearance of dead cells [5,6,11,35]. Here, we demonstrate a role of SOCS3 in mononuclear phagocytes for the regulation of efferocytosis of apoptotic/dead endothelial cells, which can modulate ex vivo angiogenesis.…”
Section: Discussionsupporting
confidence: 61%
“…Multiple pathological situations accompanied by altered angiogenesis may display the rapid accumulation of cellular debris as well as activation of microglia/macrophages [6,10]. Recently, we could even show that mononuclear phagocytes can contribute to pathological retina angiogenesis by the modulation of endothelial cell apoptosis [11]. Subsequently, these mononuclear phagocytes may also contribute to the clearance of apoptotic endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, another group suggested that VEGF and HIF-2α in astrocytes may be essential for pathological neovascularization in their OIR model [ 47 ]. The other group demonstrated that hematopoietic HIF-2α deficiency could reduce pathological neovascularization through the modulation of endothelial cell death [ 48 ]. Therefore, we think that more comprehensive studies regarding HIF subtypes as well as VEGF-producing cell types and systemic vascular cell conditions may be needed for a better understanding of pathological mechanisms for ocular neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…HIFs are heterodimers comprising two basic helix-loop-helix proteins (the HIFα and HIFβ subunits), which recognize the hypoxia response element (HRE, entailing the G/ACGTG motif) in the promoter of several genes, with major roles in different cell functions, including cellular metabolism, survival and proliferation, and in processes, such as angiogenesis, hematopoiesis and inflammation [17]. Whereas the expression of HIF1α protein is ubiquitous, the cellular expression of the HIF2α subunit is rather restricted to certain cells, for instance, cells of hematopoietic origin, ECs, adipocytes, glial cells and interstitial cells of the kidney [18,19,20,21,22,23]. While there is some functional overlap of both HIF isoforms, HIF1α and HIF2α also have distinct functions, each specifically regulating different genes.…”
Section: Hypoxia Pathway Proteinsmentioning
confidence: 99%